Radiation-Induced Sarcoma following Prolonged Coronary Stent Placement - Eric J. Vick; Christopher T. Clark; James M. Lewis (Case Reports in Surgery)
Radiation exposure for the average coronary stent placement varies based on a number of factors but typically amounts to 6–11 mSv per patient (compared to 3 mSv background). As with all procedures which utilize radiation, there is an inherent risk of genetic mutation and the possible development of malignancy. Here, we present the case of a 75-year-old male who presented with an exophytic mass on his back following prolonged coronary catheterization with a radiation burn seven years prior. Biopsy of the lesion revealed the mass was consistent with an undifferentiated pleomorphic sarcoma emanating from the site of the radiation burn. After staging studies demonstrated no evidence of metastatic disease, radical excision with negative margins was performed. This case demonstrates that despite the rarity of radiation injury, each incidence necessitates strict monitoring of radiation exposure and continual follow-up due to the risk of malignancy.